2012
DOI: 10.1002/chem.201200583
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Synthesis of Quinazolines in Water Starting from o‐Bromobenzylbromides and Benzamidines

Abstract: Water makes it possible: The Cu(2)O-catalyzed reaction between easily available o-bromobenzylbromides and benzamidines by using Cs(2)CO(3) as the base and N,N'-dimethylethylenediamine (DMEDA) as the additive in water as the solvent gives access to substituted quinazolines in a single step with yields ranging from 57 to 85 % (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 26 publications
0
74
0
Order By: Relevance
“…To further explore the potential of our methodology, we investigated the reaction of 2-bromobenzylamine (9 b) with various amidines (11 a-i), which is one of the key functional group in modern drug synthesis to construct various N-heterocycles including quinazolines. [19] To our satisfaction, catalyst 3 proved to be efficient in the CÀ N cross-coupling of benzami-…”
Section: Full Papermentioning
confidence: 77%
See 1 more Smart Citation
“…To further explore the potential of our methodology, we investigated the reaction of 2-bromobenzylamine (9 b) with various amidines (11 a-i), which is one of the key functional group in modern drug synthesis to construct various N-heterocycles including quinazolines. [19] To our satisfaction, catalyst 3 proved to be efficient in the CÀ N cross-coupling of benzami-…”
Section: Full Papermentioning
confidence: 77%
“…Moreover, our synthetic protocol has also been found suitable for the synthesis of six member N-heterocycles (quinazolines) via CÀ N cross-coupling of benzamides and amidines with 2-bromobenzylamine and 2-bromobenzylbromide respectively, under relatively mild reaction conditions. [18,19] It is worth mentioning that quinazolines are common building blocks for numerous alkaloids and functional molecules displaying a broad range of biological and therapeutic activities. [20] Consequently, over the years the synthesis of quinazolines has attracted significant attention.…”
Section: Full Papermentioning
confidence: 99%
“…Initial studies addressed the effect of temperatures on the conversion of 2-aminoacetophenone to 2-phenylquinazoline. 2,7,49,50 Scheme 1 Cyclization reaction of 2-aminoacetophenone and benzylamine using ZIF-67 catalyst. It was observed that the cyclization reaction could not occur at room temperature, with no trace amount of product aer 180 min.…”
Section: Resultsmentioning
confidence: 99%
“…No reaction occurred when the procedure was carried out in the absence of copper catalyst (Table 1, entry 18). Finally, we studied the solvent effect and found that CH 3 CN was superior to toluene, THF, PhCl, and DMF (Table 1, entries 12,[19][20][21][22]. In addition, the reaction failed to give the desired product when the procedure was carried out under a N 2 atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang reported a three-component synthesis of quinazoline derivatives using a low melting sugar-urea-salt mixture as a solvent [19]. In 2012, Beifuss and co-workers developed a copper-catalyzed coupling reaction of o-bromobenzylbromides and benzamidines for the synthesis of quinazolines in an aqueous medium [20]. The condensation reactions of 2-aminobenzylamines with aldehydes followed by subsequent oxidation with strong oxidants (e.g., 2,3-dichloro-5,6-dicyano-l,4-benzoquinone (DDQ) [21], MnO 2 [22], and NaClO [23]) provide a conventional but simple method to synthesize quinazolines (Scheme 1(a)).…”
Section: Introductionmentioning
confidence: 99%